Bat (Mammalia: Chiroptera) Diversity of the Taliwas River conservation area, Lahad Datu, Sabah - Nur Ain Awatif Mohd-Kanapiah; Lawrence Alan Bansa; Waidi Sinun; Noor Haliza Hasan (Universiti Malaysia Sabah, 2025)
Understanding species diversity and distribution is essential for informing conservation strategies, particularly in lesser-explored forest habitats. This study provides the first species checklist of bats in the Taliwas River Conservation Area (TRCA), a forest reserve adjacent to the Danum Valley Conservation Area (DVCA) in Sabah, Malaysia. A four-night bat survey was conducted from June 8–11, 2022, using mist nets and harp traps placed along three forest interior trails. A total of 16 bat species comprising 61 individuals were recorded across four families: Pteropodidae (4 spp.), Rhinolophidae (6 spp.), Hipposideridae (3 spp.), and Vespertilionidae (3 spp.). The insectivorous Hipposideros cf. saevus (formerly Hipposideros ater) was the most frequently captured species (21 individuals), while Pteropus vampyrus (n = 4) was visually observed feeding on Octomeles sumatrana (Binuang) nectar near the main camp. Two species of high conservation concern were recorded: the Endangered P. vampyrus and the Vulnerable Hipposideros ridleyi. The detection of multiple forest-interior species, including individuals showing reproductive signs, suggests that the TRCA provides suitable habitat for both foraging and roosting. These results highlight the conservation relevance of the TRCA as a complementary area to the broader DVCA landscape. Future studies incorporating long-term monitoring, acoustic detection, and habitat quality comparisons between protected and adjacent modified landscapes are recommended to inform site-based conservation management.